The taxation of petroleum and minerals : principles, problems and practice - Daniel, Philip; Keen, Michael; McPherson, Charles P. (London ; New York : Routledge/International Monetary Fund, 2010)
The book provides a comprehensive but accessible account of the core issues in the area of taxation of the oil, gas and minerals, which range from the conceptual to the very practical.
Includes bibliographical references and index.
nif 07/05/13; oif 29/07/15
Loans
Keywords: Petroleum; Mines and mineral resources; Mining leases